Protein quality of roselle (Hibiscus sabdariffa L.) seeds - Mohd Nazri, Halimatul Saadiah; Ismail, Amin; Mohd Esa, Norhaizan; Abdul Ghani, Nawalyah; Mansor, Siti Muskinah (Universiti Putra Malaysia Press, 2007)
This study investigated the protein quality of two sets of Roselle seeds processed differently (dried and boiled). Twenty weanling Sprague Dawley rats were used to conduct the growth and nitrogen balance studies. Rats were fed with 10% (w/w) protein from dried (DS) and boiled (BS) Roselle seeds powder for 4 weeks. Casein was used in this study as a standard reference protein. There was a significantly higher (p < 0.05) food intake and weight gain by rats fed with BS compared with DS. In the growth study, there was no significant difference (p < 0.05) in protein efficiency ratio (PER) and net protein ratio (NPR) of BS compared to DS, but it was significantly different with casein (CD). PER value of rats fed with DS was significantly lower (p < 0.05) than casein. In the nitrogen balance study, true nitrogen absorption (TNA) and nitrogen balance (NB) of BS group was significantly higher (p < 0.05) than DS group. However, apparent digestibility (AD), true digestibility (TD) and biological value (BV) for both diets was not significantly different. This study showed that the protein quality of dried Roselle seeds was similar to the Roselle seeds boiled at 100oC for 30 minutes.